The Greenland Ice Sheet at the peak of warming during the previous Interglacial - O. Rybak O.; F. Hoebrects; О. Рыбак О.; Ф. Хёбрехтс (Ice and Snow, 2015)
The Last Interglacial (LIG or the Eemian) between ca. 130 and 115 kyr BP is probably the best analogue for future climate warming for which increasingly better proxy data are becoming available. The volume of the Greenland Ice Sheet (GrIS) during this period is of particular interest to better assess how much and how fast sea-level can rise in a future Earth undergoing gradual climatic warming. Sea-level during the LIG is inferred to have been up to 9 meter higher than today, but contribution of the GrIS into this rise remains unclear. Various ice-sheet modeling studies have come up with a very broad range of the LIG volume loss by the GrIS to between 60 cm and 6 m of equivalent sea-level rise. This wide range is explained by the sensitivity of GrIS models to the imposed climatic conditions and to poor knowledge of the LIG climate itself in terms of the magnitude and precise timing of the maximum warming, as well as in terms of spatial and annual patterns. To partially circumvent these uncertainties we made use of the newest temperature record over the Central Greenland reconstructed from the isotopic composition of the recently obtained NEEM ice core containing undisturbed LIG segment to build the climatic forcing of the model. The NEEM record unequivocally indicates times of the start and of the end of the LIG warming in Greenland as well as the duration of the warmest time period within the Eemian. Using a three-dimensional thermomechanical ice-sheet model, we produced an ensemble of possible LIG configurations by varying only four key parameters for temperature, precipitation rate, surface melting magnitude and melting pattern within realistic bounds. The outcome of a series of the numerical experiments is a variety of glaciologically consistent GrIS geometries corresponding to a wide range of possible «climates». To constrain the ensemble of GrIS geometries, we used data inferred from 5 Greenland ice cores such as the presence or absence of LIG ice, borehole temperature and isotopic composition. Lagrangian ...